The Ideality of Electoral Democracy in Indonesia: Voting Linkage Participation and Awareness of Money Politics in the Special Region of Yogyakarta (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
One of the serious problems in democracy in Indonesia is the practice of money politics in general elections. In many ways, the practice of money politics is quite problematic. Money politics is believed to take place but is difficult to prove. This situation can be caused by the reluctance of citizens to report money politics practices. On the other hand, voter participation rates in Indonesia from time to time are quite high. In order to answer this paradox, this article tries to elaborate on citizens' interest in participating in elections with an awareness of money politics. The question to be answered is to what extent does voting participation influence awareness of money politics? This article uses Kolasse survey data in the Special Region of Yogyakarta (D.I.Y) in December 2022 and using research data conducted by the Research Center for Politics and Government (PolGov) on the Village Head Election (Pilkades) in Yogyakarta in December 2018. The analysis results show that the more someone wants to participate in voting, the more that person will not report the practice of money politics. This result is interesting, considering that D.I.Y is one of the provinces with a very high Human Development Index (HDI) among provinces. The high HDI figure shows the high quality of life in the region, which is expected to influence the quality of democracy. Likewise, qualitative research shows that the lower the level of election in Indonesia, the smaller the possibility of money politics occurring. This condition is also supported by the potential to build and strengthen political links between citizens and civil society organizations. Hopefully, this short article can contribute to sparking discussion regarding money politics. On the other hand, this paper still has shortcomings, especially regarding the importance of elaborating on the operationalization of money politics, the need for measurements using survey data with a large number of respondents and on a national scale as well as strengthening evidence in research on gaps in the use of money politics on a national and regional scale.
Keywords: Voting Participation; Money Politics; Election; Democracy